(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The aim of this article is to analyze the discursive construction of a social representation of the “nicolaitas” (regents, professors and students) fostered by the internal regulations of the Colegio de San Nicolás de Hidalgo. The main supplying of this work are, therefore, the regulations of the Colegio de San Nicolas in Morelia. At the same time, some communications between the secretary of the State Government and that of the campus were reviewed, as well as some press releases. The arguments are constructed based on Pierre Bourdieu’s approaches to representation and with some guidelines to approach the rules and practices offered by the analysis from the viewpoint of everyday school life. The main question that has been raised is how much the regulations weighed at the moment of interacting outside the school. Through discourse analysis, we reflect on how they sought to be perceived in terms of practices and values that they considered as their own, but also attached to the regulations.